KEBIJAKAN PENDIDIKAN DALAM KONTEKS GLOBALISASI - Ayumi Tampubolon; Athiyah; Nurhaliza; Muhammad Syaifuddin (Jurnal Ilmu Pendidikan Islam, 2026)
Globalization has impacted various aspects of life, including the education sector, thus demanding policies that can address the challenges and opportunities of the global era. This article aims to analyze education policy in the context of globalization, particularly as it relates to Islamic education in Indonesia. This study uses a qualitative approach with library research. Data were obtained from various literature sources, including books, scientific articles, policy documents, and relevant research findings. Data analysis was conducted using content analysis techniques to examine the development of national education policy and Islamic education in the face of globalization. The study results indicate that the government has undertaken various efforts through curriculum reform, strengthening educational standards, internationalizing higher education, developing madrasahs, transforming Islamic Religious Higher Education Institutions, and strengthening the existence of Islamic boarding schools (pesantren). On the other hand, globalization presents a number of challenges, such as the digital divide, global cultural dominance, the dichotomy of knowledge, the crisis of educational relevance, and the threat of radicalism. However, globalization also opens up opportunities in the form of broader access to learning resources, international cooperation, the use of digital technology, and the strengthening of universal Islamic values. Therefore, an adaptive, integrative education policy is needed that is oriented towards developing global competencies without ignoring Islamic identity and national values.